Translocation of a looped polymer threading through a nanopore. Issue 16 (29th March 2021) - Chen, Jia; Chen, Xian; Sun, Li-Zhen; Xu, Xiao-Jun; Luo, Meng-Bo
Abstract : Translocation of looped polymers shows six translocation pathways with different probabilities, translocation times, and current blockade profiles. The translocation of a looped polymer is different from linear or pristine loop polymers. Abstract : Recent experiments reported that the complicated translocation dynamics of a looped DNA chain through a nanopore can be detected by ionic current blockade profiles. Inspired by the experimental results, we systematically study the translocation dynamics of a looped polymer, formed by three building blocks of a loop in the middle and two tails of the same length connected with the loop, by using Langevin dynamics simulations. Based on two entering modes (tail-leading and loop-leading) and three translocation orders (loop–tail–tail, tail–loop–tail, and tail–tail–loop), the translocation of the looped polymer is classified into six translocation pathways, corresponding to different current blockade profiles. The probabilities of the six translocation pathways are dependent on the loop length, polymer length, and pore radius. Moreover, the translocation times of the entire polymer and the loop are investigated. We find that the two translocation times show different dependencies on the translocation pathways and on the lengths of the loop and the entire polymer.